The Struggle to Rebuild and Transform Higher Education in Afghanistan - Hayward, Fred M; Babury, Mohammad O. (International Higher Education, 2015)
One of the untold success stories of Afghanistan is the transformation of higher education over the last six years focusing on quality improvement, increased access, faculty development, curriculum upgrading, and merit recruitment and promotions. While some of these changes are fragile and more needs to be done, prospects for the future are encouraging.